Effects of Viloxazine ER (Qelbree®) on Weight and Height Trajectories: Interim Results From a Long-term, Open-Label Extension Trial in Pediatric ADHD. (April 2023) - Nasser, Azmi; Hull, Joseph; Earnest, Jami; Koch, Jennifer; Liranso, Tesfaye; Maldonado-Cruz, Zulane; Rubin, Jonathan; Childress, Ann
Abstract: Introduction: Stimulant medications and the norepinephrine reuptake inhibitor, atomoxetine, contain warnings regarding potential for slowing of growth (weight and height) in children and recommend monitoring of growth when using these medications for pediatric ADHD. Viloxazine ER (viloxazine extended-release capsules; Qelbree®), is a nonstimulant medication, FDA-approved for ADHD in adults and children (≥6 years of age). Viloxazine ER has pharmacologic differences from other approved ADHD medications and might not affect growth in the same manner as other therapies. A safety analysis was conducted to determine viloxazine ER effects on growth and weight trajectories in pediatric ADHD patients with long-term use. Methods: Data were evaluated from five DBPC, phase 2 and 3 clinical trials and an ongoing long-term, open-label extension (OLE) trial (NCT02736656). Viloxazine ER doses during the trials ranged from 100–400 mg/day (age 6–11 yrs) or 100–600 mg/day (age 12–17 yrs). Height and weight were evaluated pretreatment in both DB and OLE every 3 months during the OLE, and converted into percentile values and corresponding z-scores using Centers for Disease Control (CDC) normal growth curves to evaluate growth trajectories. The incidence of weight- and growth-related adverse events (AEs) terms were also evaluated. Results: At the time of data cut (31 July 2019), 1097 subjects had received at least one dose of viloxazine ER in the OLE (66% male, mean (SD) age 10.8 (3.06), 59% age 6–11, mean (SD) BMI 18.8 (3.42) kg/m 2, height 146.7 (17.46) cm, weight 42.1 (16.01) kg. During the OLE, mean (SE) z-scores for height and weight were between -1 and 1 for all timepoints, indicating growth measures within a normal range compared with expected values. Similar results were observed when weight and height were analyzed by sex and by age categories. Growth data were available for 338 subjects at 12 months. Among these subjects, the mean (SD) change from baseline in weight-for-age z-score was -0.2 (0.5) and height-for-age z-score was -0.14 (1.1). Adverse events relevant to weight and growth in the DB trials (incidence ≥ 1%) included (viloxazine ER [100–600 mg/day] n=1117 vs. placebo n=487): decreased appetite (8.1% vs. 0.8%), nausea (5.1% vs. 2.7%), vomiting (4.7% vs. 1.4%), weight increase (0.4% vs. 1.2%) and weight decrease (1.3% vs. 0.4%), and increased appetite (0.2% vs. 1.2%). During the OLE weight-and growth-related AEs reported for ≥ 1% of subjects were: decreased appetite 5.8%, vomiting 2.7%, nausea 2.4%, weight decreased 2.3%, and weight increased 2.0%. Conclusions: Over time, pediatric subjects taking viloxazine ER, on average, maintained normal weight and height relative to the CDC's child growth charts. However, because Qelbree may affect weight, it is recommended that healthcare providers check patient weight before starting and while using viloxazine ER. Funding: Supernus Pharmaceuticals, Inc.